The prehistoric human impact on slope development at the archaeological site in Smólsk (Kuyavian Lakeland) - Kittel, Piotr (Bulletin of Geography. Physical Geography Series, 2015)
Periods of intense human impact on the relief and lithology of the area of the Smólsk site were recorded during geoarchaeological research accompanying archaeological field work. The phases of occupation of the area are known in detail from the results of the large-scale archaeological research of the site. The slope deposits with buried soils were recorded at the site area and researched in detail with the use of sedimentological, geochemical and micromorphological analyses. Beside geochronological deterioration, the chronology of the artefacts found in layers played an important role in the strict recognition of the age of deposits. The lower part of the studied slope cover is constituted by deluvium and the upper part by tillage diamicton. The origin and the development of the slope deposits are correlated with the phases of an intense prehistoric human impact as defined by the archaeological research. Four main phases of acceleration of slope processes were documented at the site and date to the Early Neolithic, the Middle Neolithic, the Bronze Age and the Early Iron Age.